Pembelajaran Tematik Berbasis Media Pembelajaran Dalam Meningkatkan Mutu Siswa - Adam Nasution (Kota Bengkulu, Provinsi Bengkulu, Indonesia, 2023)
Abstract: Learning media-based thematic learning still creates difficulties among teachers, so teachers have difficulty in improving the quality of graduate students, because learning media is an intermediary or introduction to sources of messages, recipients of messages, stimulates thoughts, feelings, attention, will, is driven and involved in learning process. Some teachers have difficulty implementing thematic learning which is a form of integrated learning model that combines a concept in several materials, subjects or fields of study into a particular theme or topic of discussion where there is integration between knowledge, skills and values that allows students to actively discover scientific concepts and principles in an integrated way. holistic, meaningful and authentic. The research objective is to map and describe thematic learning based on instructional media in improving student quality. Using library research methods or literature study. The results of the study can be concluded that learning media-based thematic learning can improve student quality seen in increasing student interest and interest in the learning process. Thematic learning based on learning media can also overcome the limitations of student experience. Learning media-based thematic learning can also go beyond the classroom, embed correct, concrete and realistic concepts, and the types of learning media consist of print-based media, human-based media, visual-based media, computer-based media, so as to improve the quality of learning and student quality. Thus, it can be suggested that to improve the quality of students, apply thematic learning based on learning media in the teaching and learning process in schools. Keywords: Thematic Learning, Learning Media, Quality of Student Graduates Abstrak: Pembelajaran tematik berbasis media pembelajaran masih menciptakan kesulitan di kalangan guru, sehingga guru mengalami kesulitan dalam meningkatkan mutu lulusan siswa, dikarenakan media pembelajaran merupakan perantara atau pengantar sumber pesan, penerima pesan, merangsang pikiran, perasaan, perhatian, kemauan, terdorong dan terlibat dalam proses pembelajaran. Sebagian guru kesulitan menerapkan pembelajaran tematik yang merupakan bentuk model pembelajaran terpadu yang menggabungkan suatu konsep dalam beberapa materi, pelajaran atau bidang studi menjadi satu tema atau topik pembahasan tertentu yang terjadi integrasi antara pengetahuan, keterampilan dan nilai yang memungkinkan siswa aktif menemukan konsep serta prinsip keilmuan secara holistik, bermakna dan otentik. Tujuan penelitian memetakan dan mendeskripsikan pembelajaran tematik berbasis media pembelajaran dalam meningkatkan mutu siswa. Menggunakan metode penelitian kepustakaan atau studi pustaka. Hasil penelitian dapat disimpulkan bahwa pembelajaran tematik berbasis media pembelajaran dapat meningkatkan mutu siswa terlihat pada meningkatkatnya ketertarikan dan minat siswa dalam proses pembelajan. Pembelajaran tematik berbasis media pembelajaran juga dapat mengatasi keterbatasan pengalaman siswa. Pembelajaran tematik berbasis media pembelajaran juga dapat melampaui kelas, menanamkan konsep yang benar, kongkrit dan realistis, dan jenis media pembelajaran terdiri dari media berbasis cetakan, media berbasis manusia, media berbasis visual, media berbasis computer, sehingga dapat meningkatkan mutu pembelajaran dan mutu siswa. Dengan demikian, dapat disarankan bahwa untuk meningkatkan mutu siswa, maka terapkanlah pembelajaran tematik berbasis media pembelajaran di dalam proses belajar mengajar di sekolah. Kata Kunci: Pembelajaran Tematik, Media Pembelajaran, Mutu Lulusan Peserta Didik